Power, Narrative, and Magical Realism in Hudā Ḥamad’s Sindrīllāt Masqaṭ - Aljomaa, Mervat (Journal of Arabic Literature, 2023)
This article examines the narrative and literary techniques employed in Hudā Ḥamad’s Sindrīllāt Masqaṭ to draw on Omani women’s experiences of writing and speaking as sources of empowerment and narrative identity. Marking a shift from the dominant realistic and historical fiction often associated with male writers, Ḥamad experiments with magical realism, the carnivalesque, intertextuality, and metafiction to reconfigure the novelistic genre beyond the national prescriptions of literary production. Through the voice of the narrator, alongside the voices of other ordinary women, the novel underscores the significance of women’s symbolic practices within the societal and cultural boundaries of Oman. In an allegory of writing—a major thread running throughout the novel—the narrator/writer seeks to combine the composite, multiple, and fictional fragments of various women’s stories into a single readable text that preserves oral and cultural memory. Thus, on the one hand, this article explores the writer’s experimentation with narrative and storytelling within the context of the Omani literary tradition. On the other hand, it examines modes of women’s empowerment that work through articulative and enunciative practices in the face of linguistic frustration.
Keywords: Littérature – Oman

Counterproxy: Sonallah Ibrahim’s Warda and the revolution in Oman - Rasberry, Vaughn (Representations, 2023)
Keywords: Littérature – Oman

فضاءات الأدب العماني الحديث ‏ابحاث واقراءات و مراجعات - السمرائي, فليح مضحي (الجمعية العمانية للكتاب, 2023)
Keywords: Littérature – Oman

رحلة بتوقيت نيويورك - الوهيبي, بدر بن ناصر (الجمعية العمانية للكتاب, 2023)
Keywords: Littérature – Oman